RTI data from the project 'Bulverket', project identifiers RAÄ-2023-2419 and RAÄ-2026-0670 - Canosa, Elyse; Mårtensson, Magnus; d'Agnan, Peter (Swedish National Heritage Board, 2026)
The project focused on reflectance transofmation imaging (RTI) analysis of several wooden parts retrieved from Bulverket (https://www.geonames.org/maps/google_57.7278_18.6286.html ), an archaeological site in Tingstäde träsk (https://www.geonames.org/2669011/tingstaede-traesk.html) on Gotland. The wooden parts were taken out of the water the week before they arrived at the Heritage Laboratory at the Swedish National Heritage Board and had not been treated before analysis, but had been wrapped in plastic and stored cool to prevent drying out and mold growth. RTI imaging helped to highlight and better visualize tool marks on the surface of the objects, which can help better understand the construction, use and age of Bulverket. Included is both RTI data and an instrument report detailing the samples and the analysis parameters. Data collected was used as part of the PhD dissertation by Peter d'Agnan at Lund University. The project identifiers at the Swedish National Heritage Board are RAÄ-2023-2410 and RAÄ-2026-0670.
Keywords: Reflectance transformation imaging; RTI; Bulverket; Tingstäde träsk; Gotland; Archaeology; Heritage Science; Archaeological wood; RAÄ-2023-2410; RAÄ-2026-0670; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi